First record of Cecilioides acicula (Müller, 1774) (Mollusca: Ferussaciidae), from Buenos Aires province, Argentina - Díaz, Ana C. (2017)
Fil: Díaz, Ana C.. División Zoología Invertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina